Linkage between productivity and innovation in different service sectors - Kärt R\~oigas (OrdnungsPolitisches Portal (OPO), 2011)
The purpose of the paper is to find out whether linkages between productivity and innovation are different among Estonian service sector sub-sectors. In this paper productivity is measured as value added per employee. An original approach toward measurement of productivity is used, decomposing it into three components: labour costs, depreciation and gross profit per employee. Four types of innovation are studied: product, process, organizational and marketing innovation. The empirical analysis is based on productivity data from the Estonian Business Register and innovation data from the Estonian Community Innovation Survey 5, covering the period between 2004 and 2006. Results based on Estonian service sectors reveal that in different sub-sectors different types of innovation are linked to productivity. Still, all linkages between innovation and productivity or its components are positive. There is one exception: among assisting services marketing innovation and gross profit are negatively associated with each other.
Keywords: 330; service sector; productivity; productivity components; four innovation types; Dienstleistungssektor; Innovation; Produktivität; Schätzung; Estland